Introducing Computer Content in Nursing Education: One Experience - Newbern, Virginia B. (1982)
The Continuing Education Program of the College of Nursing, The University of Akron, offered its first credit course on computer usage in nursing and health, The Computer As a Nursing Tool, in the summer of 1978. A second course, Computer Usage in Health Care: A National Survey, was offered in the summer of 1980. This paper describes how the need for content related to computer usage was initially identified and how the content for the first course, which focused heavily on learning the language, flow charting, and much interaction with the computer, evolved. It traces the evolution of the second course which brought together nurse computer experts from many areas to share their knowledge and experience with students in an intensive week-long two credit workshop. An outline of potential resources and “helpful hints” is included. The paper closes with a discussion of how knowledge concerning the computer and its uses can be integrated into nursing education and practice.